Clinical outcome of a conservative approach to giant cell tumor of ankle and foot bones. (June 2021) - Tiwari, Akshay; Verma, Vivek; Yadlapalli, Anilkumar
Highlights: GCT foot and ankle. Curettage. Cementation. Abstract: Giant cell tumor of the bone (GCTB) affecting foot and ankle is rare, and the literature available on their clinical behavior and reconstructive options is scarce. Many authors consider these sites a special subset with high rates of local recurrence. Eighteen patients with GCTB of foot and ankle were treated from (March 2014 to February 2020). Extended curettage was offered wherever feasible. Twelve patients underwent extended curettage, three underwent resection and reconstruction, one patient had ray amputation, one had below knee amputation. One patient with multifocal disease was treated conservatively with denosumab. There were 11 females and the mean age was 31.7 years. Distal tibia (11 patients) was the commonest location, followed by the first metatarsal (four patients). At a median follow up of 46 months, two patients out of the 17 operated had a local recurrence. GCTB affecting the foot and ankle have a clinical course comparable to those at other locations. They should be treated with a conservative approach, where radical resection and amputation are reserved for only the non-curettable tumors.